ANALISIS PENGARUH INVESTASI PENDIDIKAN DAN KESEHATAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN PROVINSI SUMATERA BARAT - Risna Rahmadhani; Armida Silvia (Jurnal Ecogen, 2018)
The purpose of this research is to analyze the influence of education and health investment to economic growth in the district of west sumatera province in 2012-2016. This research uses Fixed Effect Model to process panel datas and uses Economic Growth as dependent variabel, independent variabel are education seen from mean years school and literacy rate, health seen from life expetancy and infant motality rate. The result shown that mean years school has a significant negative effect on economic growth in the district of west sumatera province, literacy rate has a positive but not significant on economic growth in the district of west sumatera province, life expetancy has a significant negative effect on economic growth in the district of west sumatera province and infant motality rate has a negative and not significant effect on economic growth in the district of west sumatera province. Keywords : Economic Growth, Mean years school, Literacy Rate, Life Expectancy, Infant Mortality Rate.